New Directions in Vernacular Security Research
XIII, 261 p. 4 illus.
Keywords: This edited collection offers new engagement with important case studies and contexts that have been neglected in the field of vernacular security research. With cutting edge scholarship from fieldwork and primary research in Georgia, Tunisia, Bangladesh, the Pacific Islands, and beyond, the book's international focus takes vernacular security research far beyond its traditional focus on migration and counterterrorism policy in the global North. Engaging with unusual and untouched sources of vernacular security knowledge such as soldiers' autobiographies, popular culture artefacts, and national security strategies, the book pushes the field into new methodological and conceptual directions. This agenda-setting collection will be essential reading to anyone interested in the everyday politics of security. Lee Jarvis is Professor of Security and Society at Adelaide University, Australia. His research focuses on the construction and communication of security challenges. Michael Lister is Professor of Politics at Oxford Brookes University, UK. His research focuses on the intersections between citizenship and terrorism/counterterrorism. Akinyemi Oyawale is an Assistant Professor in International Relations in the Politics and International Studies Department (PAIS) at the University of Warwick, UK. His research focuses on a critical interrogation of International Relations theory including its often unacknowledged raced and gendered dimensions and in how citizens construct their experiences of (in)security. .